Hair : styling tips and tricks for girls - Jordan, Jim (Jim M.), 1960- (Middleton, WI : American Girl, 2000)
Provides advice on taking care of different types of hair, instructions for a variety of hairstyles, and suggestions for all kinds of hair accessories.
"American girl library."
Keywords: Hairwork -- Juvenile literature; Hairstyles -- Juvenile literature; Braids (Hairdressing) -- Juvenile literature; Hair -- Care and hygiene -- Juvenile literature; Hair -- Care and hygiene; Hairstyles